Food riots arising from food crises in Latin America: Reflections on the 21st century agrarian context - Artur Zimerman (London School of Economics and Political Science (LSE), Department of International Development, 2023)
This paper focuses on food riots that arise in the agrarian context characterized by food crises, primarily for the rural poor in developing and undeveloped countries located in Latin America for the current century. It is a preliminary study that investigates the connection between food riots and some indicators and variables related to agrarian pressures and political strains, such as land grabbing, climate change, demographic pressures, and political polarization. The data analysis is descriptive in this initial phase of research. The Latin American region rarely features in investigations of the proposed theme, whereas Africa is widely studied, as is Asia, to a lesser extent. Latin America represents a paradox, because on the one hand it is one of the largest food producers in the world, but on the other hand, it has many citizens who do not have enough food for own consumption. The paper focuses on the violence emanating from food riots in order to understand the contexts in which it arises. Future studies may explain this phenomenon.
Keywords: 330; Food riots; agrarian violence; land grabbing; climate change; demographic pressures; political polarization